2022
DOI: 10.1186/s12884-022-04779-9
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy in Sao Tome and Principe: are there different obstetric and perinatal outcomes?

Abstract: Background Adolescent childbirth is a major public health problem in Sao Tome and Principe (STP). Adolescent pregnancy and childbirth can carry a risk of morbidity associated with the physiological and sociological characteristics of teenage girls. This study aims to identify the main adverse obstetric and perinatal outcomes for adolescent pregnancies in the Hospital Dr. Ayres de Menezes (HAM), the only hospital in STP. Methods An institution-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…These results are in line with studies conducted in Cameroon [69] and Ethiopia [36] as well as published literature that suggests that lower APGAR scores are associated with severe multiorgan damage resulting in brain damage, lung dysfunction, cardiomyopathy, renal failure, hepatic failure, necrotizing enterocolitis and consequently death [70]. Previous studies [23,24] that compared outcomes between adolescent pregnant girls and older counterparts identified that adverse outcomes imputable to adolescent births were fetal distress (OR 1.94, 95% CI 1.18-3.18) and performance of neonatal resuscitation maneuvers (OR 2.4, 95% CI1.07-5.38), highlighting the risks surrounding this period among deliveries at HAM maternity unit.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in line with studies conducted in Cameroon [69] and Ethiopia [36] as well as published literature that suggests that lower APGAR scores are associated with severe multiorgan damage resulting in brain damage, lung dysfunction, cardiomyopathy, renal failure, hepatic failure, necrotizing enterocolitis and consequently death [70]. Previous studies [23,24] that compared outcomes between adolescent pregnant girls and older counterparts identified that adverse outcomes imputable to adolescent births were fetal distress (OR 1.94, 95% CI 1.18-3.18) and performance of neonatal resuscitation maneuvers (OR 2.4, 95% CI1.07-5.38), highlighting the risks surrounding this period among deliveries at HAM maternity unit.…”
Section: Discussionsupporting
confidence: 91%
“…stillbirths excluded *Fetal distress was defined as a low Apgar score <7 at the first minute of life (score from 0 to <7) [24,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling method Sample size followed the WHO-steps approach [32] applying a web-based sample size calculator, Raosoft (http://www.raosoft.com/samplesize.html) which suggested a minimum sample size of The definition of birth asphyxia was only determined using the components of the APGAR score table [30,31] since techniques such as umbilical arterial blood gas samples from a clamped section of the umbilical cord are not available in STP. This was similarly applied to both term and preterm infants [23]. Infection as early-onset neonatal sepsis diagnosed in STP is only possible in a suspicion-based algorithm since there are no microbiologic techniques such as, blood culture, available.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, ABOs were defined as PTB, LBW, macrosomia, congenital anomaly, birth asphyxia and neonatal sepsis suspicion. This present study is included in a broader project on neonatal health and adverse outcomes [22][23][24], and the authors studied the determinants for perinatal and neonatal mortality (until the 28 th day of life) in STP in another study. This current study aimed to identify the risk factors for adverse birth outcomes among newborns delivered at the only hospital maternity unit in STP.…”
Section: Introductionmentioning
confidence: 99%